Emulsificante em dietas para frangos de corte com diferentes fontes lipídicas - TAVARES, Fernando Barbosa (Universidade Federal do Pará, 2017)
This study aimed to evaluate the effects of diets containing different lipid source and the inclusion of an emulsifier (soy lecithin and polyethylene glycol ricinoleate) for broilers. Article I aimed to evaluate the influence of different fat sources in the metabolization of nutrients and serum broiler profiles, with the addition of emulsifier. 336 chicks were used in a 4x2 factorial arrangement, with eight replications and four lipid sources (soybean oil, Poultry Oil, Fish Oil and Tallow Beef) and 2 types of inclusions (not including the product and 5 g / kg emulsifier). Proceeded metabolic tests by the total collection method. The data were subjected to analysis of variance in SAS and the means were compared by Tukey test, the significance of P <0.05. No difference was observed for feed intake, metabolization coefficient of dry matter and crude protein. The coefficient of metabolizable ether extract (CMEE) was lower in the diets of fat (P <0.001). The lipid source modifies the metabolization of diets. The emulsifier, the tested values, does not modify the metabolization of ingredients and does not modify the HDL serum parameters, LDL, Cholesterol and Triacilglerol. For Article II aimed to test how the addition of emulsifier can alter the performance parameters, metabolization, carcass composition and economic viability for broiler diets with poultry oil and beef tallow. Diets with poultry oil (OA) or tallow (SB), in treatments to control (CON), other diets with reduction of 0.83 MJ / kg of metabolizable energy (RED) and diets with reduced MS and inclusion of 0, 1% inclusion of emulsifier (Emul). Diets with poultry oil performed better on average weight and feed intake, resulting in a reduction in the amount of crude protein in the carcass of 58.3% to 56.1% in diets with SB and OA respectively. The results indicated that the emulsifier reduced metabolization of ether extract, but increased the EMA in the diet with beef tallow in 0.93 MJ / kg. The emulsifier added in the form proposed only increased the cost of diet without significant result on performance, metabolism and body composition of broilers.